MHD free convection-radiation interaction in a porous medium - Part I: Numerical investigation - Vasu, B.; Gorla, Rama Subba Reddy; Siddiqa, Sadia; Murthy, P.V.S.N.; Prasad, Ramachandra V.; Bég, Anwar O. (Zielona Góra: Uniwersytet Zielonogórski)
A numerical investigation of two dimensional steady magnetohydrodynamics heat and mass transfer by laminar free convection from a radiative horizontal circular cylinder in a non-Darcy porous medium is presented by taking into account the Soret/Dufour effects. The boundary layer conservation equations, which are parabolic in nature, are normalized into non-similar form and then solved numerically with the well-tested, efficient, implicit, stable Keller-Box finite-difference scheme.
Keywords: implicit finite difference scheme; Keller-Box method; non-Darcy porous media transport; magnetic field; horizontal circular cylinder